Treatment Method for Sewage Water Used in Horticulture - Rajest, S. Suman; Regin, R.; T, Shynu; R, Steffi. (European Journal of Life Safety and Stability (2660-9630), 2023)
The purpose of a sewage treatment plant is to take wastewater, filter it for any contaminants, and then discharge it back into the environment in a way that is safe for humans and other living things. Because improper wastewater management contributes to environmental pollution and infectious diseases can easily spread due to the presence of a variety of pathogenic organisms in wastewater, the primary goal of wastewater treatment is to enable the proper disposal of wastewater from industrial, domestic, and commercial uses without endangering human health or the environment. To treat wastewater in the conventional sense, a number of physical, chemical, and biological procedures are used to filter out nutrients, organic materials, and solid particles. When we talk about the physical, chemical, and biological properties of water, we’re talking about its quality. This metric assesses the state of water in relation to the requirements of various living organisms, whether they be humans or other non-human creatures. When referring to a collection of criteria that can be used to evaluate compliance, it is most commonly used in this context. The most popular criteria for evaluating water quality are its impact on ecosystem health, human contact safety, and potability.